2018
DOI: 10.1038/s41401-018-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

TIGAR knockdown enhanced the anticancer effect of aescin via regulating autophagy and apoptosis in colorectal cancer cells

Abstract: Our previous study showed that TP53-induced glycolysis and apoptosis regulator (TIGAR) regulated ROS, autophagy, and apoptosis in response to hypoxia and chemotherapeutic drugs. Aescin, a triterpene saponin, exerts anticancer effects and increases ROS levels. The ROS is a key upstream signaling to activate autophagy. Whether there is a crosstalk between TIGAR and aescin in regulating ROS, autophagy, and apoptosis is unknown. In this study, we found that aescin inhibited cell viability and colony formation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Nevertheless, in mouse models, the absence of TIGAR reduces capabilities to regenerate injured intestinal epithelium and represses tumor development with ROS restriction ( 50 ). TIGAR is upregulated in some cancer models and tumor types via a pattern that may be independent on the maintenance of p53 ( 51 , 52 ). Furthermore, TIGAR expression negatively correlates with p53 expression in human breast cancer ( 53 ).…”
Section: P53 Represses the Tigar Gls2 Sco2 And Sat1 Genes To Mediamentioning
confidence: 99%
“…Nevertheless, in mouse models, the absence of TIGAR reduces capabilities to regenerate injured intestinal epithelium and represses tumor development with ROS restriction ( 50 ). TIGAR is upregulated in some cancer models and tumor types via a pattern that may be independent on the maintenance of p53 ( 51 , 52 ). Furthermore, TIGAR expression negatively correlates with p53 expression in human breast cancer ( 53 ).…”
Section: P53 Represses the Tigar Gls2 Sco2 And Sat1 Genes To Mediamentioning
confidence: 99%
“…TIGAR acted as an oncogene in nasopharyngeal carcinoma (NPC) tumorigenesis, and knockdown of TIGAR inhibited tumor growth via activation of NF-κB pathway 20. Deletion of TIGAR sensitizes cancer cells to radiotherapy and chemotherapy in glioma and CRC cells 9,21. When over-expressed, TIGAR protects chronic lymphocytic leukemia (CLL) cells from spontaneous apoptosis and is closely correlated with worse clinical outcome in CLL patients 13.…”
Section: Discussionmentioning
confidence: 99%
“…Functioning like FBPase-2, TIGAR lowers intracellular fructose 2,6-biphosphate (FBP) levels, thus decreases the glycolytic rate and diverts the glucose metabolism to the pentose phosphate pathway (PPP) 8. Increased expression of TIGAR mRNA and protein was associated with cancer cell survival and metastasis in many cancers,913 while the association between plasma TIGAR concentration and CRC metastasis remains unclear. In the present study, we aimed to explore the association of plasma TIGAR concentration with CRC metastasis and the prognostic value of TIGAR as a potential marker for CRC metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…TIGAR is a multifunctional protein that is not only involved in the regulation of glucose metabolism, cell cycle progression and radiation response, but also in autophagy [17]. A number of studies have shown that autophagy is inhibited by overexpression of TIGAR and induced by knockdown of TIGAR [8,[29][30][31] and TIGAR-regulated autophagy is closely related to clinical disease. For example, TIGAR inhibits proliferation and migration of pulmonary artery smooth muscle cells (PASMCs) by inhibiting autophagy and ROS, thereby improving hypoxia-induced pulmonary arterial hypertension (PAH) [32].…”
Section: The Regulation Of Autophagy By Tigarmentioning
confidence: 99%